The HRuCCH, RuCCH2, and Ru-η2-C2H2 Molecules: Infrared Spectra and Density Functional Calculations - Wang, Qiang; Wang, Xuefeng; Andrews, Lester (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2011)
Laser-ablated ruthenium atoms undergo reaction with acetylene during condensation in excess neon and argon matrices to form a metallacycle complex, insertion into the C–H bond, and rearrangement to the vinylidene complex. The subject molecules were identified by 13C2H2 and C2D2, isotopic substitutions and density functional theory (DFT) frequency calculations. The HRuCCH molecule is described by Ru–H, CH, and CC stretching modes and CCH deformation modes. A very strong CC double bond stretching, weak CH stretching, and CCH deformation frequencies were observed for the RuCCH2 complex. The metallacycle Ru-η2-(C2H2) is characterized through CC double bond stretching, CH stretching and CCH deformation modes. The reaction mechanism for formation of the RuCCH2 complex was investigated by B3LYP internal reaction coordinate calculations, and the hydrido-alkyny complex is the rate-determining step. The delocalized three-center-four-electron π bond using the Ru 4d xz electron pair contributes to the C–C π* orbital and provides stabilization energy (ΔE (2), second-order perturbation) for the vinylidene RuCCH2 complex.